Screening and Education on Obesity at the Siko Community Health Center in Ternate City - Eko Sudarmo Dahad Prihanto; Rabiatul Adawiyah Sidi Umar; Asilia Ayunda Purnawan (Riviera Publishing, 2026)
Obesity is a serious global health problem with increasing prevalence, posing risks of metabolic complications such as diabetes mellitus, hypertension, and cardiovascular disease. Delayed diagnosis and lack of public knowledge are common challenges in obesity management. This community service initiative aims to perform early screening for obesity and central obesity among outpatients at the Siko Community Health Center in Ternate City, followed by educational guidance to achieve optimal treatment outcomes and prevent complications. Screening for obesity and central obesity was conducted among 50 outpatients, followed by personalized education using informational leaflets. The results showed that 26 participants (52%) had obesity, and 29 (58%) had central obesity. Metabolic comorbidities associated with obesity were found in 44% of cases, with hypertension being the most prevalent (26%). In conclusion, this community service activity revealed high prevalence rates of obesity and central obesity, and education on obesity management was successfully provided to all participants.